"Prvi general ujet od nas" - Kocjančič, Klemen (Studia Historica Slovenica, 2017)
Author, using critical analysis and interpretation of archival material and literature, presents life and death of Dr. Konrad Heidenreich, high-ranking official of German construction Organisation Todt, who was in rang of military general. After career as an architect, working on several famous construction project of the Third Reich, he, after the start of Second World War, joined Organisation Todt, where he was supervising construction projects right until the last month of the war, when he was captured and executed by the partisans in Slovenia. He is considered as the first German, holding a title equivalent to a rank of a military general, which was captured by Slovenian partisans before the general capitulation of the Third Reich.
Keywords: druga svetovna vojna; generali; Heidenreich, Konrad; Nemci; NOB; Slovenija; svetovna vojna 1939-1945; vojni ujetniki